PERAN ENTREPRENEURSHIP TERHADAP KINERJA IKM DI KABUPATEN GIANYAR (STUDI KASUS PADA IKM KERAJINAN PATUNG BATU PADAS) - I Nyoman Wahyu Widiana; Imakulata Dada Gole; I Nyoman Supartha (Fakultas Ekonomi dan Bisnis Universitas Wijaya Putra, 2022)
The small and medium industry sector is a sector that has various roles in improving the economy in Gianyar Regency, Bali Province. Gianyar Regency is famous for its handicraft/artist culture that has the potential and contributes to the development of large, medium or small scale industries. The development of Small and Medium Industries (IKM) continues to increase. One of the small and medium industries that are of concern is the stone sculpture industry. Therefore, a research was conducted with the title of the role entrepreneurship on the performance of IKM in Gianyar Regency (a case study on IKM stone sculpture crafts). The purpose of this study was to determine the role entrepreneurship on the performance of IKM Batu Padas based on three factors, namely innovation, creativity and the ability to take risks on the performance of SMEs in Gianyar Regency. The type of research used in this research is the type of quantitative research using descriptive methods. The process of collecting research data using a questionnaire distribution technique to 55 respondents and processed using SPSS. The measurement scale used in this study is the Likert scale. Measurements for the independent and dependent variables use a scoring to assign a value to each alternative answer so that the data can be calculated. The results of this study indicate that innovation has a positive and significant effect on the performance of IKM in Gianyar Regency. Creativity has a positive and significant effect on the performance of IKM in Gianyar Regency, Risk has a positive and significant impact on the performance of IKM in Gianyar Regency, Innovation. Creativity and risk have a significant influence on the performance of the Batu Padas SMI in Gianyar district.